Associations and potential epigenetic changes between air pollution and osteoarthritis risk and survival: Insights from a prospective cohort study - Jing Qian; Jiahao Zhu; Yifan Wang; Ruoqi Dai; Jingyou Miao; Ye Yang; Wenxia Zhao; Jing Wang; Lilu Ding; Dan Zhou; Min Yu; Yingjun Li (Ecotoxicology and Environmental Safety)
Background: The influence of air pollution on osteoarthritis (OA) remains underexplored. Methods: We conducted a prospective cohort study in the UK Biobank, estimating exposure levels of particulate matter (PM2.5, PM10, PM2.5–10), nitrogen oxides (NO2, NOx), and air pollutants exposure score (APES). Cox models assessed associations between air pollution exposure and OA incidence, joint replacement, and survival. Additionally, using genome-wide association statistics, we examined the potential causal associations between air pollution-related DNA methylation (DNAm) and OA risk. Gene-environment interaction analyses were conducted to explore the potential modification effect of DNA methylation-related genetic variants on the impact of air pollution on OA risk. Results: Individual exposure to each air pollutant was associated with an increased risk of developing OA, but not with progression from OA to joint replacement. For APES, the hazard ratio for incident OA was 1.09 (95 % CI = 1.04–1.13), and the hazard ratio of progression from OA to death was 1.16 (95 % CI = 1.00–1.35) in the highest quartile group compared to the lowest quartile group. Moreover, genetically predicted methylation at the PM2.5-related CpG site cg04027612 near the GDF5 gene was associated with a lower risk of OA. A potential epigenetic modification effect of cg04027612 near GDF5 on OA risk was observed. Conclusion: Long-term exposure to air pollution was associated with an increased risk of OA in the population and poorer survival outcomes for OA patients, with epigenetic changes in GDF5 potentially playing a role in the underlying mechanisms.